Microtus xanthognathus - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
143. Taiga Vole Microtus xanthognathus French: Campagnol a joues jaunes / German: Gelbwangen-Wihlmaus / Spanish: Topillo de taiga Other common names: Chestnut-cheeked Vole, Yellow-cheeked Vole Taxonomy. Arvicola xanthognatha [sic] Leach, 1815, Hudson Bay, Manitoba, Canada. This species is monotypic. Distribution. C Alaska, USA, E across Yukon, W Northwest Territories, extreme NW British Columbia, N & C Alberta, N Saskatchewan, and N Manitoba to W Hudson Bay, Canada. Descriptive notes. Head-body 141-173 mm, tail 45-53 mm, hindfoot 24-— 27 mm; weight 140-170 g. The Taiga Vole is large and distinctive, with orange or yellow color near snout and whiskers. Dorsum is dark sepia to bister (brownish yellow), with coarse black hair. Venter is dusky gray. Juveniles are dark gray. Skull is ridged and angular and has large bullae. Nasals and incisive foramina are elongated and narrow. M” has three closed triangles; M, has two nearly enclosed triangles. Chromosomal complement is 2n = b4, FN = 62. Habitat. Early successional forests and along mesic forest edges, with heavy moss or ground cover for burrowing and an abundant source of horsetail (Equisetum sp., Equisetaceae) or Epilobium (Onagraceae) rhizomes for food. In Alaska, Taiga Voles are often found 5-10 years after a burn in black spruce (Picea mariana, Pinaceae) forests, often with substantial understory. Food and Feeding. Taiga Voles eat cached rhizomes in winter and feed heavily on grasses, horsetail, and berries in summer. Breeding. Taiga Voles breed in May-September. Young are born in underground burrows. Young-of-the-year do not breed until the following year. Litters have 6-13 young (average 8:8), and females have 1-2 litters/year. Taiga Voles are polygynous, and males maintain territories. Activity patterns. Taiga Voles are terrestrial. Movements, Home range and Social organization. Taiga Voles construct partially subterranean runways, often located near water. Communal nests are shared by 5-10 individuals in winter. Nests have multiple entrances, and nearby ...